The effect of a mixed cannabidiol and cannabidiolic acid based oil on client‐owned dogs with atopic dermatitis. Issue 4 (29th May 2022) - Loewinger, Melissa; Wakshlag, Joseph J.; Bowden, Daniel; Peters‐Kennedy, Jeanine; Rosenberg, Andrew
Abstract: Background: Cannabidiol (CBD) and cannabidiolic acid (CBDA) are reported to have antinociceptive, immunomodulatory and anti‐inflammatory actions. Objectives: To determine if CBD/CBDA is an effective therapy for canine atopic dermatitis (cAD). Animals: Thirty‐two privately owned dogs with cAD. Materials and methods: Prospective, randomised, double‐blinded, placebo‐controlled study. Concurrent therapies were allowed if remained unchanged. Dogs were randomly assigned to receive either 2 mg/kg of an equal mix of CBD/CBDA (n = 17) or placebo for 4 weeks. On Day (D)0, D14 and D28, Canine Atopic Dermatitis Extent and Severity Index, 4th iteration (CADESI‐04) and pruritus Visual Analog Scale (pVAS) scores were determined by investigators and owners, respectively. Complete blood count, serum biochemistry profiles and cytokine bioassays were performed on serum collected on D0 and D28. Results: There was no significant difference in CADESI‐04 from D0 to D14 ( p = 0.42) or D28 ( p = 0.51) in either group. pVAS scores were significantly lower for the treatment group at D14 ( p = 0.04) and D28 ( p = 0.01) and a significant change in pVAS from baseline was seen at D14 ( p = 0.04) and not D28 ( p = 0.054) between groups. There was no significant difference in serum levels of interleukin (IL)‐6, IL‐8, monocyte chemoattractant protein ‐ 1, IL‐31 or IL‐34 between groups at D0 or D28. Elevated alkaline phosphatase was observed in four of 17 treatment group dogs. Conclusions and clinical relevance: CBD/CBDA as an adjunct therapy decreased pruritus, and not skin lesions associated with cAD in dogs. Abstract : Background – Cannabidiol (CBD) and cannabidiolic acid (CBDA) are reported to have antinociceptive, immunomodulatory and anti‐inflammatory actions. Objectives – To determine if CBD/CBDA is an effective therapy for canine atopic dermatitis (cAD). Conclusions and clinical relevance – Cannabidiol/CBDA as an adjunct therapy decreased pruritus, and not skin lesions associated with cAD in dogs. Résumé: Contexte ‐ Le cannabidiol (CBD) et l'acide cannabidiolique (CBDA) auraient des actions antinociceptives, immunomodulatrices et anti‐inflammatoires. Objectifs – Déterminer si le CBD/CBDA est une thérapie efficace pour la dermatite atopique canine (cAD). Animaux – Trente‐deux chiens de propriétaires privés atteints de cAD Matériels et méthodes – Étude prospective, randomisée, en double aveugle, contrôlée versus placebo. Les thérapies concomitantes étaient autorisées si elles restaient inchangées. Les chiens ont été répartis au hasard pour recevoir soit 2 mg/kg d'un mélange égal de CBD/CBDA (n = 17) soit un placebo pendant quatre semaines. Aux jours (J)0, J14 et J28, les scores Canine Atopic Dermatitis Extent and Severity Index, 4th iteration (CADESI‐04) et prurit Visual Analog Scale (pVAS) ont été déterminés respectivement par les investigateurs et les propriétaires. Une formule sanguine complète, des profils biochimiques sériques et des dosages biologiques des cytokines ont été réalisés sur le sérum prélevé à J0 et J28. Résultats – Il n'y avait pas de différence significative au CADESI‐04 de J0 à J14 ( P = 0, 42) ou J28 ( P = 0, 51) dans les deux groupes. Les scores pVAS étaient significativement inférieurs pour le groupe de traitement à J14 ( P = 0, 04) et J28 ( P = 0, 01) et un changement significatif de la pVAS par rapport à l'inclusion a été observé à J14 ( P = 0, 04) et non à J28 ( P = 0, 054) entre les groupes. Il n'y avait pas de différence significative dans les taux sériques d'interleukine (IL)‐6, IL‐8, protéine chimiotactique des monocytes‐1, IL‐31 ou IL‐34 entre les groupes à J0 ou J28. Une phosphatase alcaline élevée a été observée chez quatre des 17 chiens du groupe de traitement. Conclusions et pertinence clinique ‐ Le CBD/CBDA en tant que traitement d'appoint a diminué le prurit, et non les lésions cutanées associées à la DAC chez les chiens. Resumen: Introducción ‐ se ha descrito que el cannabidiol (CBD) y el ácido cannabidiólico (CBDA) tienen acciones antinociceptivas, inmunomoduladoras y antiinflamatorias. Objetivos ‐ determinar si el CBD/CBDA es una terapia eficaz para la dermatitis atópica canina (CAD). Animales ‐ Treinta y dos perros de propietarios privados con cAD Materiales y métodos – Estudio prospectivo, aleatorio, doble ciego, controlado con placebo. Se permitieron terapias concurrentes si permanecían sin cambios. Los perros fueron asignados al azar para recibir 2 mg/kg de una mezcla igual de CBD/CBDA (n = 17) o placebo durante cuatro semanas. En el día (D)0, D14 y D28, los investigadores y los propietarios determinaron las puntuaciones del índice de extensión y gravedad de la dermatitis atópica canina, cuarta revisión (CADESI‐04) y la escala análoga visual de prurito (pVAS), respectivamente. Se realizaron hemogramas completos, perfiles bioquímicos séricos y bioensayos de citoquinas en suero obtenido en D0 y D28. Resultados ‐ no hubo diferencias significativas en CADESI‐04 de D0 a D14 ( P = 0, 42) o D28 ( P = 0, 51) en ninguno de los grupos. Las puntuaciones de pVAS fueron significativamente más bajas para el grupo de tratamiento en D14 ( P = 0.04) y D28 ( P = 0.01) y se observó un cambio significativo en pVAS desde el inicio en D14 ( P = 0.04) y no en D28 ( P = 0.054) entre grupos . No hubo diferencias significativas en los niveles séricos de interleuquina (IL)‐6, IL‐8, proteína quimioatrayente de monocitos‐1, IL‐31 o IL‐34 entre los grupos en D0 o D28. Se observó fosfatasa alcalina elevada en cuatro de los 17 perros del grupo de tratamiento. Conclusiones y relevancia clínica ‐ CBD/CBDA como terapia adjunta disminuyó el prurito y no las lesiones cutáneas asociadas con la CAD en perros. Zusammenfassung: Hintergrund – Eine antinozizeptive, immunmodulatorische und entzündungshemmende Wirkung von Cannabidiol (CBD) und Cannabidiolsäure (CBDA) ist beschrieben. Ziele – Es sollte festgestellt werden, ob CBA/CBDA eine wirksame Therapie für die atopische Dermatitis (cAD) des Hundes darstellt. Materialien und Methoden – Es handelt sich um eine prospektive, randomisierte, doppelblinde, Plazebo‐kontrollierte Studie. Begleitende Behandlungen waren erlaubt, sofern sie nicht verändert wurden. Die Hunde wurden zufällig eingeteilt, um entweder 2 mg/kg einer gleichen Mischung von CBD/CBDA (n = 17) oder Plazebo vier Wochen lang zu erhalten. Am Tag (D) 0, D14 und D28 wurden mittels Canine Atopic Dermatitis Extent and Severity Index, 4 th iteration (CADESI‐04) bzw Pruritus Visual Analog Scale (pVAS) entsprechende Werte durch UntersucherInnen bzw BesitzerInnen bestimmt. Es wurden ein großes Blutbild, Serum Biochemie und Zytokin Assays am Serum, welches an D0 und D28 genommen wurde, durchgeführt. Ergebnisse – Es bestand in keiner der Gruppen ein signifikanter Unterschied des CADESI‐04 zwischen D0 und D14 ( P = 0, 42) oder D28 ( P = 0, 51). pVAS Werte waren in der Behandlungsgruppe am D14 ( P = 0, 04) und am D28 ( P = 0, 01) signifikant niedriger und eine signifikante Veränderung der pVAS Basiswerte zwischen den Gruppen wurde am D14 ( P = 0, 04) und nicht am D28 ( P = 0, 054) gefunden. Es bestand kein signifikanter Unterschied zwischen den Serumwerten von Interleukin (IL)‐6, IL‐8, Monozyten Chemoattractant Protein‐1, IL‐31 oder IL‐34 zwischen den Gruppen am D0 oder D28. Es wurden bei Hunden in vier der 17 Behandlungsgruppen erhöhte Werte der Alkalischen Phosphatase gefunden. Schlussfolgerungen und klinische Bedeutung – CBD/CBDA als Zusatztherapie verminderte den Juckreiz, aber nicht die Hautveränderungen, die mit cAD bei Hunden einhergehen. 要約: 背景 ‐ カンナビジオール (CBD) およびカンナビジオール酸 (CBDA) は、抗侵害受容作用、免疫調節作用、抗炎症作用を有すると報告されている。 目的 – 本研究の目的は、CBD/CBDAが犬アトピー性皮膚炎 (cAD) に対して有効な治療法であるかどうかを明らかにすることであった。 被検動物 ‐ cAD を有するオーナー所有犬 32 頭 材料と方法 ‐ 前向き無作為化二重盲検プラセボ対照試験。併用療法は、変化がない場合は許可された。犬はCBD/CBDAの等量混合物2mg/kg(n = 17) またはプラセボのいずれかを4週間投与するよう無作為に割り当てられた。D0、D14およびD28に、犬アトピー性皮膚炎の程度および重症度指数 (CADESI‐04)、痒みのビジュアルアナログスケール (pVAS) スコアをそれぞれ調査員、飼い主が決定した。D0とD28に採取した血清について、全血球数、血清生化学プロファイル、サイトカイン・バイオアッセイ法を実施した。 結果 ‐ CADESI‐04のD0からD14(P = 0.42) またはD28(P = 0.51) まで、いずれの群でも有意差はなかった。pVASスコアはD14(P = 0.04) およびD28(P = 0.01) で治療群に有意に低く、ベースラインからのpVASの有意変化はD14(P = 0.04) で見られ、D28(P = 0.054) では認められなかった。インターロイキン (IL)‐6、IL‐8、単球走化性タンパク質‐1、IL‐31、IL‐34の血清レベルには、D0とD28で群間に有意な差はなかった。アルカリフォスファターゼの上昇が17頭中4頭で観察された。 結論および臨床的意義 ‐ CBD/CBDAを補助療法として投与することで、cADに関連する皮膚病変ではなく、犬の痒みを減少させることができた。 摘要: 背景‐据报告, 大麻二醇(CBD)和大麻二酚酸(CBDA)具有镇痛、免疫调节和抗炎作用。 目的‐确定CBD/CBDA是否是犬特应性皮炎(cAD)的有效疗法。 动物‐32只患有cAD的私家犬。 材料和方法‐前瞻性、随机、双盲、安慰剂对照研究。如果保持不变, 允许合并治疗。将犬随机分配至2 mg/kg CBD/CBDA等混合物组(n = 17)或安慰剂组, 持续4周。在第(D)0天、第14天和第28天, 由研究者和犬主人分别测定犬特应性皮炎程度和严重指数、第4版(CADESI‐04)和瘙痒视觉模拟量表(pVAS)评分。对D0和D28采集的血清进行全血细胞计数、血清生化特征和细胞因子生物测定。 结果‐两组中从D0至D14(P = 0.42)或D28(P = 0.51)的CADESI‐04无显著差异。治疗组在D14(P = 0.04)和D28(P = 0.01)的pVAS评分显著降低, 在D14(P = 0.04)而非D28(P = 0.01)观察到pVAS相对于基线的显著变化.054) 。D0或D28时, 组间血清白细胞介素(IL)‐6、IL‐8、单核细胞趋化蛋白‐1、IL‐31或IL‐34水平无显著差异。在17只治疗组犬的4只中观察到碱性磷酸酶升高。 结论和临床相关性–CBD/CBDA作为辅助治疗减少了犬中的瘙痒, 而对cAD相关的皮肤病变无效。 Resumo: Contexto – O canabidiol (CBD) e ácido canabidiólico (CBDA) são relatados como tendo ações antinociceptivas, imunomoduladoras e anti‐inflamatórias. Objetivos – Determinar se CBD/CBDA é eficaz no tratamento da dermatite atópica canina (CAD) Animais ‐ Trinta e dois cães de propriedade privada com DAC. Materiais e métodos ‐ Estudo prospectivo, randomizado, duplo‐cego, placebo‐controle. As terapias concomitantes foram permitidas se permanecessem inalteradas. Os cães foram divididos aleatoriamente em dois grupos, o que receberia 2 mg/kg de uma mistura igual de CBD/CBDA (n = 17) ou placebo durante quatro semanas. No Dia (D) 0, D14 e D28, o Índice de Extensão e Gravidade da Dermatite Atópica Canina, 4ª iteração (CADESI‐04) e os escores da Escala Visual Analógica de Prurido (pVAS) foram determinados pelos investigadores e proprietários, respectivamente. Hemograma completo, perfis bioquímicos séricos e ensaios de citocinas foram realizados no soro coletado em D0 e D28. Resultados ‐ Não houve diferença significativa no CADESI‐04 de D0 a D14 ( P = 0, 42) ou D28 ( P = 0, 51) em nenhum dos grupos. Os escores de pVAS foram significativamente menores para o grupo de tratamento no D14 ( P = 0, 04) e D28 ( P = 0, 01) e observou‐se uma alteração significativa no pVAS do D0 comparado ao D14 ( P = 0, 04) e não ao D28 ( P = 0, 054) entre os grupos. Não houve diferença significativa nos níveis séricos de interleucina (IL)‐6, IL‐8, proteína quimiotática de monócitos‐1, IL‐31 ou IL‐34 entre os grupos em D0 ou D28. Elevação na fosfatase alcalina foi observada em quatro dos 17 cães do grupo de tratamento. Conclusões e relevância clínica – CBD e CBDA como uma terapia adjuvante é capaz de reduzir prurido, mas não lesões cutâneas associadas à DAC em cães.